External quality assurance of malaria nucleic acid testing for clinical trials and eradication surveillance - Murphy, S; Hermsen, C; Douglas, A; Edwards, N; Petersen, I; Fahle, G; Adams, M; Berry, A; Billman, Z; Gilbert, S; Laurens, M; Leroy, O; et al. (Public Library of Science, 2014)
Nucleic acid testing (NAT) for malaria parasites is an increasingly recommended diagnostic endpoint in clinical trials of vaccine and drug candidates and is also important in surveillance of malaria control and elimination efforts. A variety of reported NAT assays have been described, yet no formal external quality assurance (EQA) program provides validation for the assays in use. Here, we report results of an EQA exercise for malaria NAT assays. Among five centers conducting controlled human malaria infection trials, all centers achieved 100% specificity and demonstrated limits of detection consistent with each laboratory's pre-stated expectations. Quantitative bias of reported results compared to expected results was generally <0.5 log10 parasites/mL except for one laboratory where the EQA effort identified likely reasons for a general quantitative shift. The within-laboratory variation for all assays was low at <10% coefficient of variation across a range of parasite densities. Based on this study, we propose to create a Molecular Malaria Quality Assessment program that fulfills the need for EQA of malaria NAT assays worldwide.